Basolateral Amygdala Serotonin 2C Receptor Regulates Emotional Disorder-Related Symptoms Induced by Chronic Methamphetamine Administration - Zhuo Wang; Chen Li; Jiuyang Ding; Yanning Li; Zhihua Zhou; Yanjun Huang; Xiaohan Wang; Haoliang Fan; Jian Huang; Yitong He; Jianwei Li; Jun Chen; et al. (Frontiers Media S.A., 2021)
Globally, methamphetamine (MA) is the second most abused drug, with psychotic symptoms being one of the most common adverse effects. Emotional disorders induced by MA abuse have been widely reported both in human and animal models; however, the mechanisms underlying such disorders have not yet been fully elucidated. In this study, a chronic MA administration mouse model was utilized to elucidate the serotonergic pathway involved in MA-induced emotional disorders. After 4 weeks of MA administration, the animals exhibited significantly increased depressive and anxious symptoms. Molecular and morphological evidence showed that chronic MA administration reduced the expression of the 5-hydroxytryptamine (5-HT) rate-limiting enzyme, tryptophan hydroxylase 2, in the dorsal raphe and the concentrations of 5-HT and its metabolite 5-hydroxyindoleacetic acid in the basolateral amygdala (BLA) nuclei. Alterations in both 5-HT and 5-HT receptor levels occurred simultaneously in BLA; quantitative polymerase chain reaction, western blotting, and fluorescence analysis revealed that the expression of the 5-HT2C receptor (5-HT2CR) increased. Neuropharmacology and virus-mediated silencing strategies confirmed that targeting 5-HT2CR reversed the depressive and anxious behaviors induced by chronic MA administration. In the BLA, 5-HT2CR-positive cells co-localized with GABAergic interneurons. The inactivation of 5-HT2CR ameliorated impaired GABAergic inhibition and decreased BLA activation. Thus, herein, for the first time, we report that the abnormal regulation of 5-HT2CR is involved in the manifestation of emotional disorder-like symptoms induced by chronic MA use. Our study suggests that 5-HT2CR in the BLA is a promising clinical target for the treatment of MA-induced emotional disorders.